School-based drug education: the shaping of subjectivities. Issue 1 (27th May 2014) - Bennett, Cary
Abstract : Purpose: – The purpose of this paper is to explore how school-based drug education programmes in Australia have sought to reduce adolescent drug use. Design/methodology/approach: – Drawing on insights from Foucault's later works and writers on governmentality, the paper considers how, through the use of various technologies, techniques and strategies, students have been encouraged to problematise their understanding of self by way of a series of choices they are required to make in relation to recreational drug use. Findings: – Drugs are positioned as a key factor in the psychic and social well-being of youths insofar as their health and personal happiness is said to depend on the decisions they make concerning their use of drugs. In the process, moral and political objectives are met as students internalise norms, values and objectives consonant with a self-disciplined, self-governing society. Practical implications: – By bringing into question school-based drug education, a space is created for further discussions around this historically controversial strategy. Social implications: – What is common to all school-based drug education programmes is that the problem is conceptualised in terms of individual and interpersonal deficiencies or inadequacies. Conceptualised thus, both the problem and the solution lay with the individual; it is the individual who must change. Originality/value: – The focus of this paper has not been on why school-based drug education is needed or how to improve it (the focus of most research on the subject), but rather on the methods employed to influence student use of recreational drugs. By identifying how school-based drug education has sought to shape student subjectivities, this paper has exposed specific moral and political dimensions of the project.